The Effectiveness of Eco-Descriptive Text to Increase Student’s English Reading Skill at Senior High School 1 Maronge (e-Journal of Linguistics, 2023)
This research purposed to find out the student’s reading comprehensionby the types of eco-descriptive texts to increase student's Englishreading skills at senior high school 1 Maronge. Themethod of this research of this research applied quasi-experimentalresearch The sampling technique used cluster random samplingtechnique, which the total sample of this research is 63 students. Datacollection techniques used are observation and testing. In addition, thetest implemented the pre-test and post-test design. Techniques foranalyzing data used descriptive statistical tests and paired sample t-tests. Furthermore, The results of the sample paired t-test showed thatthe sig. (2-tailed) which is 0.000, the df value is 230, the tcount value is-59.786 which has a positive meaning of 59.786, and the mean value ofpaired differences is -36.801. So, it can be concluded that sig. (2-tailed)is 0.000 ttable 1.653. This means that thereis a significant effect on the use of Eco-Descriptive Text to IncreaseStudents' English Reading through posttest and pretest.